A 3D interactive model and atlas of the jaw musculature of Alligator mississippiensis. - Casey M Holliday; Henry P Tsai; Rebecca J Skiljan; Ian D George; Sami Pathan (PLoS ONE, 2013)
Modern imaging and dissemination methods enable morphologists to share complex, three-dimensional (3D) data in ways not previously possible. Here we present a 3D interactive model of the jaw musculature of the American Alligator (Alligator mississippiensis). Alligator and crocodylian jaw musculature is notoriously challenging to inspect and interpret because of the derived nature of the feeding apparatus. Using Iodine-contrast enhanced microCT imaging, a segmented model of jaw muscles, trigeminal nerve, brain and skull are presented as a cross-sectional atlas and 3D, interactive pdf of the rendered model. Modern 3D dissemination methods like this 3D Alligator hold great potential for morphologists to share anatomical information to scientists, educators, and the public in an easily downloadable format.